PREDIKSI KEPUTUSAN INVESTASI DARI GRAFIK CANDLESTICK DENGAN MENGGUNAKAN INDIKATOR TEKNIKAL (Studi Pada Indeks Kompas100 Periode 2020-2022) - Ariska Widya Puspitasari; Shinta Permata Sari (ITB AAS INDONESIA, 2024)
Share prices will continue to experience up and down movements according to supply and demand. Therefore, investors need to carry out analysis before making investment decisions. This research aims to determine the effect of technical analysis on investment decisions. This research is quantitative research using secondary data obtained from candlestick charts on the tradingview website. The population in the research are companies whose shares are listed on the Kompas100 index for the 2020-2022 period. The sampling technique used is purposive sampling with a total sample of 142 companies. The analysis method in this research is multinomial logistic regression using SPSS version 25 application program. The research results show that Moving Average Convergence Divergence (MACD), Relative Strength Index (RSI), Bollinger Band (BB), and Parabolic SAR (PSAR) have an effect on investment decisions.